Eye tracking analysis of EAP Students' regions of interest in computer-based feedback on grammar, usage, mechanics, style and organization and development. (July 2019) - El Ebyary, Khaled; Windeatt, Scott
Abstract: Much research has been carried out on the effect of feedback on written work, although, as an individual, private, process, how a student actually engages with feedback messages is hard to investigate. Eye-tracking technology can provide useful access to that process, and is used in the current study to examine how students on a 6 week English language and study skills programme at a UK University engage with feedback provided by an Automated Writing Evaluation program. As part of their writing class they spent 2 h each week in a computer laboratory submitting essay drafts to Criterion, receiving automated feedback, and submitting second drafts. Eye-tracking was used with four students to examine which errors they focused on, what feedback comments they appeared to read, in which order and for how long, and explanations for the patterns observed were sought using stimulated recall together with a questionnaire. The results suggest that regardless of the number of errors made in each language area, there was a marked tendency to focus on comments on grammar, and on organization and development rather than usage, mechanics and style. This focus appeared to be influenced by past educational experience, motivation and writing purpose.